Analisis Diskriminan Pada Faktor-Faktor yang Memengaruhi Perilaku Peduli Lingkungan Masyarakat Kecamatan Pinolosian - Djafar, Fikriyanto; Payu, Muhammad Rezky Friesta; Abdussamad, Siti Nurmardia (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study examines the factors that distinguish the environmental awareness behavior of the Pinolosian District community using Discriminant Analysis. The low level of environmental awareness in this region is reflected in the minimal community participation in cleanliness and waste management activities. This study aims to develop a discriminant model based on three main variables, namely attitude, subjective norms, and behavioral control, and to identify the most dominant variables in distinguishing between groups of people who do and do not engage in environmentally conscious behavior. Data were obtained from 371 respondents through a questionnaire that had been tested for validity and reliability, then analyzed using R Studio software. The results show that the discriminant function formed is statistically significant, with behavioral control as the most dominant distinguishing factor, followed by subjective norms and attitudes. The resulting classification model has an accuracy rate of 69%, which indicates a fairly good ability to categorize community environmental behavior. These findings confirm that improving environmentally conscious behavior needs to focus on strengthening the community's perception of their capabilities through the provision of supporting facilities, the reduction of structural barriers, and the strengthening of social norms as the basis for formulating environmental policies at the regional level.